AKUNTANSI DEPOSITO (ANALISIS PERLAKUAN AKUNTANSI DEPOSITO BERJANGKA PADA SEKTOR PERBANKAN: STUDI LITERATUR, DATA EMPIRIS, DAN PENERAPAN PSAK) - Faza Salbillah Kusnadi; M.Fikri Hafidz; Hazizen Karnando (UM. Bengkulu, 2024)
The development of the banking industry demands reliable financial reporting as a form of management accountability to stakeholders. One vital component of a bank's financial statements is time deposits, which constitute the second-largest source of third-party funds after savings. This article aims to analyze the accounting treatment of deposits, from recognition, measurement, presentation, and disclosure, based on the Indonesian Financial Accounting Standards (PSAK). The research employed a qualitative descriptive approach, supported by a literature review, supported by data from previous research. The analysis indicates that deposit recording must adhere to the basic accrual principle, where deposit interest is recognized as interest expense and recorded as a liability until maturity. Empirical data from various journals also indicates that deposit accounting policies significantly impact bank profitability and financial ratios. This article concludes that compliance with accounting standards in deposit recording is crucial to prevent distortion of financial information. Keywords: Deposit Accounting, PSAK 50 & 55, Third-Party Funds, Banking Financial Statements.